Claudin-18.2 immunohistochemical evaluation in pancreatic cancer specimens: review and recommendations for routine testing and scoring - Luchini, Claudio; Matkowskyj, Kristina A.; Kuwata, Takeshi; Longacre, Teri A.; Schirmacher, Peter; Takamatsu, Manabu; Rüschoff, Josef; Fassan, Matteo (Virchows Archiv, 2025)
The evaluation of claudin-18 (CLDN18) by immunohistochemistry (IHC) has already entered routine diagnostic activity as a predictive biomarker for patients with gastric and gastroesophageal junction adenocarcinomas. Of note, the CLDN18 gene encodes for 2 isoforms, claudin-18.1 (CLDN18.1) and 18.2 (CLD18.2). Recent evidence has shown CLDN18.2 can be expressed in a relatively high rate of cases of pancreatic ductal adenocarcinoma (PDAC). Based on these findings, preclinical research has been conducted, and clinical trials are currently underway testing anti-CLDN18.2 targeted regimens for patients affected by locally advanced unresectable and metastatic PDAC. Notably, the therapeutic strategies with specific antibodies are directed against CLDN18.2, while the antibody for IHC recognizes both isoforms, CLDN18.1 and CLDN18.2. Since CLDN18.1 is not expressed in the stomach or in the pancreas, IHC for CLDN18 in these sites can be considered specific for the isoform CLD18.2. At this time, no specific practical testing or interpretation guidelines have been proposed in this setting. However, there are several preanalytical and analytical variables and key potential pancreas-specific pitfalls, such as the frequently diffuse and strong CLDN18.2 expression in PDAC precursors, which will likely interfere with adequate CLDN18 staining and interpretation. To overcome these issues and steer the standardization of CLDN18 evaluation within the PDAC framework, this manuscript provides practical guidance on CLDN18 testing and scoring. The adoption of a standardized approach will help align all the efforts, both in research and clinical trial settings to optimally guide the most appropriate patients for anti-CLDN18.2 targeted therapies in PDAC.